Affective and Restorative Valences for Three Environmental Categories. Issue 3 (December 2014) - Martínez-Soto, Joel; Gonzales-Santos, Leopoldo; Barrios, Fernando A.; Lena, Maria E. Montero-López
The present study evaluated images of environments in three categories with different affective and restorative valences through two computerized assessments. A non-verbal computerized response scale and the Mexican Scale of Environmental Restoration Perception were employed. 104 students assessed the affective qualities of 117 images (47 natural, 37 urban with nature, and 33 built-up without nature) according to pleasure and activation dimensions. Then 96 students assessed 54 images with high and low valence for their restorative quality. Natural images were found to generate positive affective reactions of liking and activation and high restorative quality. Affective responses to urban with nature environments tended to be positive with moderate restorative quality. Built-up without nature environments were perceived as less pleasant and had low restorative quality. However, among built-up without nature environments, some settings with striking architectural qualities evoked positive affective valences.